Comparison of potential cytotoxicity and genotoxicity of selected antidotes against organophosphates inhibiting acetylcholinesterase - Svobodová, Hana; Jošt, Petr; Štětina, Rudolf (Vojenské zdravotnické listy, 2011)
Organophosphorous compounds cause fatal intoxication based on inhibition of acetylcholinesterase, an essential enzyme of neurosynapses and neuromuscular junctions. There is an obvious need to develop appropriate treatment against them due to their application in agriculture and chemical industry or their misuse in terrorist or war attack. In the Czech army some medicaments have been established to be used against this poisoning; Obidoxime, Methoxime, Atropine and Benactyzine. In present in vitro study we focused on potential cytotoxic and genotoxic effect evaluation of these drugs by the clonogenic and comet assay, respectively. Obtained results show that oximes exhibit pronounced toxic effect, namely obidoxime in term of genotoxicity and methoxime in term of cytotoxicity.
Keywords: financování organizované; DNA Damage; Hep G2 Cells; antidota; buňky Hep G2; Benactyzine; Atropine; oximy; otrava organofosfáty; In Vitro Techniques; analýza kolonii tvořících jednotek; Time Factors; časové faktory; techniky in vitro; Methoxime; Antidotes; otrava; Financing, Organized; Poisoning; Colony-Forming Units Assay; Obidoxime; poškození DNA; Oximes; Comet Assay; organofosfáty; reaktivátory cholinesterasy; kometový test; Organophosphate Poisoning; Organophosphates; Cholinesterase Reactivators